GE_GERICHTE C/28095/2017 vom 11. Februar 2019 - GE Cour de justice (2019)
BAIL À LOYER ; LOGEMENT ; VICE DE FORME ; NULLITÉ ; PRINCIPE DE LA BONNE FOI | CPC.311.al1; CO.253; CO.18.al1; CO.271a.al1.lete; CO.271.al1; CPC.157